Study of Bacterial L-asparaginase and Molecular expression of l-asparaginase gene in Escherichia coli - Mannaa Ibrahim, Luay (International Journal of Psychosocial Rehabilitation, 2024)
E. coli remains highly active even after it is removed from the blood, possibly by sequestration by liver cells) the half-life of the enzyme is increased when lymphoma cells are implanted in guinea pigs. Since then, several microorganisms were evaluated to obtain an L-asparaginase with greater antitumor activity compared to that produced by E. coli and that was produced in an economically viable way. It is considered that the new L-asparaginases to be used as medication must have pharmacological activity causing minimal side effects. Thus, it is expected that they present a high affinity for the substrate, a half-life time sufficient to avoid administration of several doses, low immunogenicity and high stability. It was also postulated that a low cross-glutaminolytic activity is important to avoid excessive side effects of the enzyme treatment. Various information can be extracted from the simulation trajectory, such as the energy of interaction between residues from the catalytic site of an enzyme and its substrate (intermolecular) or interactions that one or more generated mutations may have with neighboring residues within the protein (intramolecular) .In the Total Potential Energy equation, we can see that the first three terms refer to: the bond length, the angles between the atoms and the bond twist, respectively. The fourth term of the equation refers to the calculation for non-directly bonded atoms and for atoms whose interaction is intermolecular, thus considering the van der Waals and Coulomb interactions